A natural experiment of industrial policy: Floriculture and the metal and engineering industries in Ethiopia - Mulu Gebreeyesus (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Ethiopia represents an excellent case study of recent industrial policy experimentation in Africa. The country is well known for its successful promotion of the cut-flower industry through business-government co-ordination. What is less known is that at nearly the same time it was also using co-ordination to promote the metal and engineering industry with little success. This study provides comparative analysis of the policy process and outcomes of the interventions in these two industries. Examining why one intervention worked and the other failed in the same political context and institutional setting provides a natural experiment to draw valuable lessons.
Keywords: O25; O55; 330; industrial policy; state-business co-ordination; Ethiopia; Africa